2023
DOI: 10.6007/ijarbss/v13-i2/15581
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Stress among University Students in The Situation of Covid-19

Abstract: Students' life at university is very chaotic and challenging in the situation of COVID-19. Thus, investigating the stress-protective factors can potentially benefit the students and their academic life. Hence, considering Emotional intelligence (EI) may play a vital role in understanding students' stress. The present study is very crucial as a lack of emotional intelligence in such an unstable situation of COVID-19 may lead to possible failure that can negatively impact students' well-being and future. The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…At the outset, the study demonstrated a positive correlation between emotional intelligence and the level of academic stress experienced by health sciences students. These ndings are consistent with several research that sought to examine the correlation between emotional intelligence and academic stress [8] [34] [49] [50]. For instance, a recent study by Majeed et al looked at the relationship between Malaysian university students' perceived stress and emotional intelligence.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…At the outset, the study demonstrated a positive correlation between emotional intelligence and the level of academic stress experienced by health sciences students. These ndings are consistent with several research that sought to examine the correlation between emotional intelligence and academic stress [8] [34] [49] [50]. For instance, a recent study by Majeed et al looked at the relationship between Malaysian university students' perceived stress and emotional intelligence.…”
Section: Discussionsupporting
confidence: 87%
“…For instance, a recent study by Majeed et al looked at the relationship between Malaysian university students' perceived stress and emotional intelligence. The study discovered a strong relationship between university students' perceptions of stress and emotional intelligence dimensions [34]. Another study conducted among 119 undergraduate students from university of Kerala reported a moderate positive correlation between emotional intelligence and academic stress [33].The ndings aligned with those observed in college students from Pakistan, Morocco, Bangladesh, and Spain [51] [31] [52] [53].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations